Formations and properties PHOTOCATALYTICally active thick films with dioxide titanium - N. V. Gaponenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The paper reports on terbium-related photo-, cathode-, and under X-ray luminescence in yttrium alumina composites Y3Al5O12 and YAlO3. The composite Y3Al5O12 was fabricated using the sol-gel method in a form of powder followed by its pressing in a tablet. The composite YAlO3 was formed in the pores of anodic alumina film grown on silicon wafer. The possibility of application both of the method for high resolution X-ray film convertor is discussed.